San Joaquin College of Law Graduation Ceremony at Veterans' Memorial Auditorium - Watkins, Howard::::::::: (1987)
Faculty on stage with Justice Hollis Best speaking at lectern. Front row: Dean Jan Pearson, Judge Dennis Caeton, Annette Leifer, John Loomis, ??, Judge James Ardaiz, Kathy Hart, ??, and Justice Charles Hamlin